Yield Loss Due to Leaf Rust on Barley at Different Sowing Dates - Getaneh Woldeab (Pest Managment Journal of Ethiopia, 2023)
Yield loss studies on barley due to barley leaf rust (BLR), caused by Puccinia hordeiOtth., were conducted for three years between 1994 and 1996 at Ambo Plant Protection Research Centre of the Institute of Agricultural Research. A susceptible variety ‘Trompillo’ was used. The experiments were conducted in a split plot design with four sowing dates assigned to main plots and fungicide unsprayed and sprayed treatments to subplots. Means of disease severity for unsprayed treatments ranged from AUDPC 661-1278 while that o f the sprayed treatments were 0.0. Late planting had a negative effect on grain yield (GY) and thousand kernel weight (TKW). Moreover, the fungicide unsprayed treatments were significantly lower in GY, TKW and kernels per spike (KPS) as compared to the sprayed treatments. Interaction effects between sowing date and fungicide treatments were also significant. Differences between unsprayed and sprayed treatments increased in all selected yield parameters as the sowing date was delayed. The losses in GY due to BLR for the four sowing dates ranged from 6.9 to 40.2 percent; for TKW from 5.9 to 27.6 percent and for KPS from 0 to 16.5 percent. Under normal sowing date (June 16), the losses for GY, TKW and KPS were 23.4, 14.3 and 0.2 percent, respectively. There were highly significant negative correlations between BLR severity and GY, and between BLR and TKW. These results confirm the economic importance of BLR on barley at Ambo.